Low reynolds propellers for increased quadcopters endurance - Carvalho, Isa Diana de Sousa Baptista Morais (2014)
With this MSit c. Dissertation in Aeronautical Engineering is intended to contribute to the research and development of long endurance quadcopters. In this dissertation, initially, the topic study is introduced and the principals components (propeller, motor and battery) for greater autonomy quadcopters are described along with the advances made by the aeronautical sector in this strand and the possible applications. Posteriorly, a description of the program used for the analysis of existing propellers and new designs is given, and its validation is performed with the experimental data set of an existing propeller, the propeller APC Slow Flyer 10x7 made available by UIUC propeller database. Then, analysis of a lower pitch propeller, the APC Slow Flyer 11x4.7 is presented and used, as the point of reference for the creation of an improved long endurance quadcopter propeller. The process of creation of a new propeller is thoroughly described, from the conceptual approach, the airfoil selection, the design for minimum induced loss with QMIL, to the respective analysis realized on the program JBLADE and the respective comparison between the propellers in question: the base propeller and the created propeller.